Surgical vs interventional radiology drainage of neck abscesses in pediatric patients. (January 2023) - Dunya, Gabriel; Keefe, Katherine Rose; Orb, Quin; Smith, Marshall E.; Park, Albert H.
Abstract: Objective: To compare outcomes using an open surgical incision and drainage (S-ID) versus an aspiration under interventional radiology drainage (A-ID) of pediatric neck abscesses. The primary outcome measure was successful drainage requiring one intervention, and the secondary outcome measures were readmission rates and overall cost to the healthcare system. Methods: Retrospective data collection of all pediatric patients treated at the Primary Children's Hospital for neck abscess from 2008 to 2020. Patients who did not require drainage were not included. Comparison between S-ID and A-ID was performed according to the primary and secondary outcomes. Results: Two hundred fifty nine patients were included in the study. Twenty-six patients had A-IR and 234 patients had S-ID. Patient demographics were not significantly different between both groups. Overall length of stay was greater in the A-ID group (5 vs 3.3 days) (p < 0.05). A second procedure was more frequent in the A-ID group with 11/26 (42%) versus 12/234(5%) in the S-ID group (P = 0.001) even after controlling for multiple possible confounding factors. The rate of readmission was also higher in the A-ID group with 3/26 (11%) versus 7/234 (3%) in the S-ID group (P = 0.006). Both groups showed similar overall cost (P = 0.621). Conclusions: A-ID and S-ID are both methods to treat head and neck abscess requiring drainage. However, overall results indicate a higher rate of failure requiring a second intervention and a higher rate of readmission in the A-ID group. In our study cost was noted to be similar between both methods.